PENINGKATAN DISIPLIN, SISTEM INFORMASI SUMBER DAYA MANUSIA DAN KOMPETENSI TERHADAP PENINGKATAN KUALITAS LAYANAN INTERNAL APARATUR SIPIL NEGARA DI PEMERINTAH KOTA MEDAN - Simanjuntak, Alida; Panjaitan, Ferry (Jurnal Manajemen dan Bisnis, 2021)
This study aims to determine the effect of increasing discipline, human resource information systems and competence on improving the quality of internal services of state civil servants in the city government of Medan, implementing a good human resource information system that is in accordance with established regulations certainly provides various conveniences and benefits. for ASN. The research method in this research is using descriptive analysis method and verification analysis. The population in this study were all state civil servants who worked in the Medan city government, except those working in the education office, health office and also those in the sub-district office. The results of this study are as follows: Partially disciplinary variables, HR information system variables, competency variables have a positive and significant influence on the quality of internal services in the city government of Medan, Simultaneously the discipline variables, information systems and competencies have a positive and significant effect on internal service quality. in the government of the city of Medan.